2014
DOI: 10.1097/bot.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Musculoskeletal Imaging in Trauma Patients

Abstract: The number of diagnostic imaging tests, radiation dose, and related charges in trauma patients increased over time at both trauma centers, with CT scans accounting for most of the radiation dose and costs. A shift toward more advanced imaging from conventional projection radiography was noted at both trauma centers. Effective dose per patient more than doubled over the course of study at center 1. By 2008, half of all radiographic studies were for musculoskeletal purposes. Previous studies have suggested an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Computed tomography employs ionizing radiation for image acquisition, and the radiation doses imparted to patients are higher from CT than from radiographs. 59 When clinically indicated, CT should be utilized, but principles of radiation safety must be followed. The organs of pediatric patients are exquisitely sensitive to radiation, and a child’s longer life expectancy yields a lengthier period of time during which he or she could potentially develop a radiation-induced cancer.…”
Section: Physeal Imagingmentioning
confidence: 99%
“…Computed tomography employs ionizing radiation for image acquisition, and the radiation doses imparted to patients are higher from CT than from radiographs. 59 When clinically indicated, CT should be utilized, but principles of radiation safety must be followed. The organs of pediatric patients are exquisitely sensitive to radiation, and a child’s longer life expectancy yields a lengthier period of time during which he or she could potentially develop a radiation-induced cancer.…”
Section: Physeal Imagingmentioning
confidence: 99%
“…A delicate balance exists between image quality and radiation exposure in the evaluation of orthopaedic trauma patients. [1][2][3][4][5][6][7] The ability to characterize unique fracture patterns and musculoskeletal anatomy has significantly im-proved with advances in computed tomography (CT) techniques. 1,[8][9][10][11][12][13][14][15] However, the collective radiation burden sustained by the population has also increased substantially.…”
Section: Introductionmentioning
confidence: 99%
“…1,[8][9][10][11][12][13][14][15] However, the collective radiation burden sustained by the population has also increased substantially. 3,7,[16][17][18][19] Distal femur fractures make up 3% to 6% of all femoral fractures and present a considerable challenge in surgical planning. 20 Up to 38% of distal femur fractures are associated with coronal plane fractures of the femoral condyles (Hoffa fractures) and require specific fixation techniques to obtain acceptable outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 However, advanced imaging with computed tomography (CT) scans in the setting of trauma have increased significantly, doubling between 2002 and 2008 alone, and provides superior spatial resolution and the ability to better evaluate the osseous morphology for preoperative planning. 17 While magnetic resonance imaging (MRI) is the modality of choice for evaluating soft tissue structures, it is less commonly used in these cases as it is more expensive and time-consuming. Despite being an ideal bone imaging study, CT scan has also been shown to reliably demonstrate soft tissue entrapment within fractures.…”
mentioning
confidence: 99%